Financial stability policies for shadow banking - Tobias Adrian (Federal Reserve Bank of New York, 2014)
This paper explores financial stability policies for the shadow banking system. I tie policy options to economic mechanisms for shadow banking that have been documented in the literature. I then illustrate the role of shadow bank policies using three examples: agency mortgage real estate investment trusts, leveraged lending, and captive reinsurance affiliates. For each example, the economic mechanisms are explained, the potential risks emanating from the activities are described, and policy options to mitigate such risks are listed. The overarching theme of the analysis is that any policy prescription for the shadow banking system is highly specific to the particular activity.
Keywords: E44; G00; G01; G28; 330; shadow bank policies; systemic risk; financial intermediation